Design and fabrication of a low-cost and programmable dip coating machine. (October 2022) - Dunlap, Christy; Featherstone, Skylar; Smith, Matthew; Vu, Man; Williams, Amanda; Bailey, Jason; Hu, Han
Graphical abstract: Abstract: Dip coaters provide a compact device that can be used to obtain uniform and consistent coatings on a substrate. This article describes a less costly dip coater design with similar specifications to other dip coaters. The machine consists of a NEMA 23 stepper motor, touch screen display, and acrylic housing to protect the substrate from dust. The machine is programmed using Arduino IDE, allowing for easy changes to be made. The small size of the dip coater makes it ideal for use in labs. The majority of the components require no alterations after purchase, allowing for easy replacements and construction.